Digestive performance of sludge with different crop straws in mesophilic anaerobic digestion. (October 2019) - Chen, Yongdong; Zhao, Ziyan; Zou, Huijing; Yang, Haifeng; Sun, Tong; Li, Mingxing; Chai, Hongxiang; Li, Li; Ai, Hainan; Shi, Dezhi; He, Qiang; Gu, Li
Graphical abstract: Highlights: Hydrolytic performances of different crop straws-added systems were analyzed. Experimental BMPs of different crop straws were cleared. Lignocellulosic texture and composition affect their hydrolysis and methanogenesis. Hemicellulose is beneficial to the enrichment of acidogens and acetogens. Abstract: This study evaluated the digestive performance of excess sludge and different crop straws. Methane production, hydrolytic and acidogenic performance of different substrates were specially focused. Results showed that wheat straw presented the highest experimental biochemical methane potential (BMP, 462.5 mL/g VSremoval ). Corn cob-added digester obtained the highest VS removal (68.8%) and the lowest methane content due to its high hemicellulose content. Kinetic studies showed that addition of crop straws could shorten the lag phase and accelerate the hydrolysis of substrates. 3DEEM results indicated that lignocellulosic compositions play important roles in sludge hydrolysis, while FE-SEM analysis showed that the lignocellulosic textures of different crop straws determine their hydrolytic performances. Microbial community and diversity results showed that the crop straws in sludge provided abundant nutrients and their unique structures supplied attachment points for microorganisms, which ensured the efficient operation of digestive process.